Adhesion Properties of Food-Associated Lactobacillus plantarum Strains on Human Intestinal Epithelial Cells and Modulation of IL-8 Release - Garcia-Gonzalez, Natalia; Prete, Roberta; Battista, Natalia; Corsetti, Aldo (Frontiers in Microbiology, 2018)
Food-associated microbes can reach the gut as viable cells and interact with the human host providing potential health benefits. In this study, we evaluated the impact on cell viability and the adhesion ability of 22 Lactobacillus plantarum strains, mainly isolated from fermented foods, on a Normal-derived Colon Mucosa cell line. Furthermore, due to the presence of mucus layer on the gut epithelium, we also investigated whether the mucin could affect the microbial adhesion property. Our results demonstrated that all the strains displayed a strong ability to adhere to host cells, showing a strain-dependent behavior with preference for cell edges, that resulted not to be affected by the presence of mucin. Based on interleukin-8 release of intestinal cells induced by some Lactobacillus plantarum strains, our data suggest a potential cross-talk with the host immune system as unconventional property of these food-associated microbes.